Analysis of Elementary School Students' Learning Readiness in the Implementation of Differentiated Learning - Matsuri, Matsuri; Atmojo, Idam Ragil Widianto; Saputri, Dwi Yuniasih; Kholifah, Cindy Nur (Mimbar Sekolah Dasar, 2024)
This study analyzes the learning readiness of elementary school students in implementing differentiated learning, on grade IV-VI students in Cluster 1 Puntadewa, Serengan District, Surakarta City. Differentiated learning involves modifying content, processes, and products according to student's readiness, interests, and learning profiles. This study uses a descriptive quantitative approach with data obtained through a learning readiness scale. The population in this study consists of students in grades IV–VI from elementary schools in the Puntadewa 1 Cluster, Serengan District, Surakarta City, for the 2023/2024 academic year. The sampling technique used was cluster random sampling, which included two schools: SD Negeri Kartodipuran and SD Muhammadiyah 14. The learning readiness scale in this study consisted of 40 statement items covering four aspects of learning readiness: (1) physical readiness, (2) psychological readiness, (3) material readiness, and (4) attitude and knowledge. The results showed that students had varying levels of learning readiness, which were divided into three categories: high, medium, and low. Differentiated learning helps students with high learning readiness achieve better results than those with medium and low learning readiness. The implications of this study support the use of differentiated learning strategies to improve the effectiveness and inclusiveness of learning.